Penyebab Terjadinya Penyakit Pneumonia Pada Balita di Wilayah Kerja Puskesmas Rawat Inap Benjina Kecamatan Aru Tengah Kabupaten Kepulauan Aru - Belliytra Talarima; Suherman Orno (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2020)
Pneumonia is inflammation of the pulmonary parenchyma in which the acini is filled with inflammatory fluid with or without infiltration of inflammatory cells into the wall of the alfeoli and interstitial cavity, which is characterised by coughing with rapid breathing and / or shortness of breath in children under five. Pneumonia causes inflammation of the lungs which makes breathing tight and litlle oxygen intake. Pneumonia is a disease caused by microorganism pneumococcus, staphylococcus, streptococcu and viruses that can be transmitted through the air medium, spit saliva, direct contact through the mouth and through contact with objects that are shared. This study aims to determine the factors that are associated with the incidence of pneumonia in infants in the work area of the Inpatient Health Center of Benjina. This type of research is analytical with a cross sectional study design. The number of samples in this study is 126. Data analysis was done in univariate and bivariate. The results of bivariate analysis showed factors related to the incidence of pneumonia in children under five in this study, namely : Knowledge of the mother (p value = 0,023) and exclusive breastfeeding (p value 0,024) while unrelated factors are exposure to cigarette smoke (p-value = 0,027), nutritional status (0,082). From the results of this study, it can be concluded that : There is a relationship between the knowledge of mothers and pneumonia incidence in children under five, there is a relationship between exclusive breastfeeding and the incidence of pneumonia in infants, there is no relationship between exposure to cigarette smoke and the incidence of pneumonia in infants, there is no relationship between status nutrition with the incidence of pneumonia in infants. Suggestion : Communities, especially mothers of children under five years old, are expected to pay attention to the health of children under five and participate in prevention and control of pneumonia in children under five so that children can avoid pneumonia, Health workers are expected to prioritize health services for children under five and provide information on the dangers of pneumonia in infants handling pneumonia in infants so that toddlers avoid pneumonia, Need for further research on factors related to the incidence of pneumonia in children under five so that they can find out other factors related to the incidence of pneumonia in infants.